The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/14659891.2019.1572804
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances of substance use by street youth in Egypt support the case for intervening to prevent adverse childhood experiences

Abstract: Background: Egyptian street youth use substances including tobacco, illicit drugs, and pharmaceutical drugs. To understand the circumstances, including adverse childhood experiences, that place adolescents at risk for engaging in substance use, we conducted in-depth interviews among a sample of Egyptian street children. Methods: From youth residing at or attending Caritas, a non-profit organization, which provides shelter and education to street youth, seven girls and twelve boys, aged 12 to 18 years, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(40 reference statements)
2
1
0
Order By: Relevance
“…The possible reason might be the parent’s difficulty in setting boundaries and communicating in the family nucleus, which leads the youth to be problematic substance users ( 36 ). This study is consistent with a study that was done in Egypt ( 37 ). An important role of professionals involved with this population is, therefore, to understand and intervene with the family’s social network to prevent migration to the streets due to family conflict.…”
Section: Discussionsupporting
confidence: 93%
“…The possible reason might be the parent’s difficulty in setting boundaries and communicating in the family nucleus, which leads the youth to be problematic substance users ( 36 ). This study is consistent with a study that was done in Egypt ( 37 ). An important role of professionals involved with this population is, therefore, to understand and intervene with the family’s social network to prevent migration to the streets due to family conflict.…”
Section: Discussionsupporting
confidence: 93%
“…This may be related to many factors as genetic mutations, as alterations of the brain structure, within the same context, people could also be genetically more likely to exhibit problems like impulsivity, executive dysfunction, and poor emotion regulation skills that will increase their risk for using substances. This result was congruent with Amr et al,(2019), who reflected that (42.4%) of street youth reported positive family history of substance use. Also, Rabie et al, (2020), reported that male and feminine students had a positive family history of nicotine, cannabis, and benzodiazepine use.…”
Section: Discussionsupporting
confidence: 82%
“…So, it is urgent to move for stopping their spreading and control the addictive cases. [1] Machine learning technology is now useful in medical data analysis. Several types of research have been carried out for the diagnosis of these cases medically.…”
Section: Introductionmentioning
confidence: 99%